2016
DOI: 10.1002/ajim.22678
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ compensation filings of temporary workers compared to direct hire workers in Illinois, 2007–2012

Abstract: There are differences between temporary workers and direct hire employees in terms of total workers' compensation awards, total time off, and percent disability. Additional studies are needed to validate these findings. Am. J. Ind. Med. 60:11-19, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 15 publications
4
30
2
Order By: Relevance
“…This study found that injured temporary agency workers in the OHBWC database were younger, more predominantly male, had less tenure (especially those with less than a year on the job), and had higher rates of injury for all MO and LT claims compared to permanently employed workers. All of the above findings concur with similar studies conducted using WC data from WA (2003‐2006, 2005‐2011, 2011‐2015); WC data from IL (2007‐2012), injury data from Spain (2001‐2002); and injury data from Finland (1997‐2007) . A recent BLS report also indicated that temporary agencies have higher proportions of younger workers, especially age 20 to 24 and that the workers tend to be male (52.3%) .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This study found that injured temporary agency workers in the OHBWC database were younger, more predominantly male, had less tenure (especially those with less than a year on the job), and had higher rates of injury for all MO and LT claims compared to permanently employed workers. All of the above findings concur with similar studies conducted using WC data from WA (2003‐2006, 2005‐2011, 2011‐2015); WC data from IL (2007‐2012), injury data from Spain (2001‐2002); and injury data from Finland (1997‐2007) . A recent BLS report also indicated that temporary agencies have higher proportions of younger workers, especially age 20 to 24 and that the workers tend to be male (52.3%) .…”
Section: Discussionsupporting
confidence: 85%
“…Of relevance, are studies that utilized WC data from WA L&I, and data from the IL WC Commission . Compared to this study, the studies from WA L&I covered, relatively shorter periods of time: 4, 5, and 7 years; and the study from Illinois covered 6 years.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations